Rapid Diagnosis of Mumps Virus Infections by Immunofluorescence Methods - Lennette, David A. (1975)
Mumps and its complications, particularly meningoencephalitis, is an important disease problem, and more rapid diagnostic methods are desirable. A study was made of immunofluorescence methods for the early detection of mumps virus isolated in cell cultures, or adsorbed directly from clinical specimens onto guinea pig erythrocytes. A specific diagnosis could be made in hours to 2 or 3 days utilizing immunofluorescence methods, in contrast to about 6 days by standard methods. Details of the direct immunofluorescence methods are presented, to encourage wider application in clinical virology laboratories.